Say I have a relation called PAPER = {ID, Title, Description, No.Students, Quarter}
.
If I say ID -> Title
and {Title, Quarter} -> No.Students
. Is there an axiom that permits me to say {ID, Quarter} -> No.Students
?
Because if id determines title, can't I just replace title with id in the second functional dependency?
One of the additional rules derived from Armstrong's axioms is the rule of pseudo-transitivity. It states that
If A->B and BC->D then AC->D.
Substituting your terms . . .
If ID->Title and {Title, Quarter}->No.Students, then {ID, Quarter}->No.Students